Artificial Intelligence Readiness in Educational Management - Nurul huda; Moh. Nasir (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
The development of Artificial Intelligence (AI) has driven significant transformation in educational systems, particularly in educational management, which requires organizational readiness and adaptive leadership to respond to digital change. However, the implementation of AI in Indonesia still faces several challenges, including low levels of digital literacy, limited technological infrastructure, and the lack of optimal leadership strategies in education. This study aims to analyze the level of AI Readiness in educational management and to examine leadership strategies and organizational readiness of schools in responding to AI-based educational transformation. This research employs a Systematic Literature Review (SLR) approach by analyzing relevant scholarly literature from reputable international journals and credible academic sources. The findings indicate that organizational readiness is influenced by several key factors, including human resource competencies, technological infrastructure, digital leadership, organizational culture, and policy support. In addition, digital leadership plays a crucial role in fostering innovation and strengthening sustainable organizational readiness. This study contributes by proposing an integrative conceptual model that combines AI Readiness, Digital Leadership, and Organizational Readiness as a strategic framework for developing AI-based educational management. The findings are expected to provide valuable insights for policymakers and educational practitioners in designing more adaptive and sustainable digital transformation strategies in Indonesia.